2020
DOI: 10.2196/18897
|View full text |Cite
|
Sign up to set email alerts
|

Conversations and Medical News Frames on Twitter: Infodemiological Study on COVID-19 in South Korea

Abstract: Background SARS-CoV-2 (severe acute respiratory coronavirus 2) was spreading rapidly in South Korea at the end of February 2020 following its initial outbreak in China, making Korea the new center of global attention. The role of social media amid the current coronavirus disease (COVID-19) pandemic has often been criticized, but little systematic research has been conducted on this issue. Social media functions as a convenient source of information in pandemic situations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(228 citation statements)
references
References 40 publications
5
200
0
7
Order By: Relevance
“…The reasons for this choice are twofold. First, many studies have already characterized public response during current and past health emergencies through the lens of Twitter [ 25 , 58 , 60 , 85 , 86 , 103 , 104 ]. Second, several studies have reported a high prevalence of bots as drivers of low-quality information and discussions on COVID-19 on this platform [ 24 , 25 , 105 - 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this choice are twofold. First, many studies have already characterized public response during current and past health emergencies through the lens of Twitter [ 25 , 58 , 60 , 85 , 86 , 103 , 104 ]. Second, several studies have reported a high prevalence of bots as drivers of low-quality information and discussions on COVID-19 on this platform [ 24 , 25 , 105 - 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Themes of previous studies that focus on exploration of, description of, correlation of, or predictive modeling with Twitter data during COVID-19 pandemic include sentiment analysis [17,[25][26][27][28], public attitude/interest measurement [21,[29][30][31], content analysis [15,[32][33][34][35][36], topic modeling [16,26,27,[37][38][39][40], analysis of misinformation, disinformation, or conspiracies [20,[41][42][43][44][45][46], outbreak detection or disease nowcasting/forecasting [18,19], and more [47][48][49][50][51][52]. Similarly, data from other social media channels (e.g., Weibo, Reddit, Facebook) or search engine statistics are utilized for parallel analyses related to COVID-19 pandemic as well [53][54][55][56][57][58][59][60][61]…”
Section: Going Beyond Correlationsmentioning
confidence: 99%
“…Creating tools to harness this pre-existing information to investigate new ideas can be considered an implementation of big data research, which is a growing area of interest [11]. Some areas of big data research include sourcing data from social media [12] and YouTube videos [13]. More recently, researchers have focused on using big data information to evaluate trends in the current COVID-19 pandemic [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some areas of big data research include sourcing data from social media [12] and YouTube videos [13]. More recently, researchers have focused on using big data information to evaluate trends in the current COVID-19 pandemic [12], [14], [15].…”
Section: Introductionmentioning
confidence: 99%